Outdoor Learning Methods on the Ability to Write Free Poetry in Hankuk University of Foreign Studies Malay-Indonesian Study Program Students South Korea - Tundreng, Syarifuddin; Sulaeman, Agus; Hoon, Kim Dong; Putra, Eko; Rofi’i, Agus (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2024)
This study aims to determine the effect of using outdoor learning methods on the ability to write free poetry in Audio Visual A1 and A2 classes of Malay-Indonesian. The method used is an experimental method of the Quasi Experimental type using two classes, namely the experimental class of 37 students which given treatment in the form of outdoor learning methods and a control class of 35 students which was not given treatment as a comparison class. The data collection technique used a poetry writing essay test and a questionnaire to find out students' responses to the outdoor learning method. Based on the results of hypothesis testing data analysis using the t test at a significant level of 0.05, a T count of 2.592 and a T table of 1.997 are obtained. Because T count is greater than T table, namely 2.592 > 1.997. It can be concluded that accept H1, reject H0, thus it can be said that there is an influence on the use of outdoor learning methods. Based on the results of hypothesis testing data analysis using the t test at a significant level of 0.05, a T count of 2.592 and a T table of 1.997 are obtained. Because T count is greater than T table, namely 2.592 > 1.997. It can be concluded that accept H1, reject H0, thus it can be said that there is an influence on the use of outdoor learning methods.the ability to write free poetry for students of the Malay-Indonesian study program Hankuk University of Foreign Studies South Korea.